Protection of the Dignity of the Corpse: A Study on the Criminalization of Necrophilia Reviewed from the Maqashid Syariah - Isnawan, Fuadi (KRTHA BHAYANGKARA, 2024)
Necrophilia in Indonesia has not been specifically regulated in the law. This causes a legal vacuum to punish the perpetrators of necrophilia in Indonesia. this research focuses on examining maqashid sharia in the criminalization of necrophilia in Indonesia. The research method used is normative research method. the results show that in Islamic teachings, necrophilia is considered a serious violation of the honor of the corpse which is highly respected, equivalent to respect for the living. This act not only violates the honor of the corpse but also the principle of keeping private parts and sight, which is emphasized in Islam. Criminalizing necrophilia protects individuals from heinous crimes and preserves the moral and ethical values of society in accordance with maqasid al-shariah, which aims to protect human honor and posterity. In the Qur'an, Allah SWT strictly prohibits zina, including all forms of sexual relations outside the bonds of legal marriage, as in Surah Al-Isra' verse 32. Necrophilia, as a sexual perversion, is a grave violation of Islamic teachings that emphasize respect for the human body. This prohibition emphasizes the importance of private parts and morality in the context of marriage and Islamic moral values. Necrophilia tarnishes human dignity, disrupts social order, and violates sharia law and Islamic ethics. Maqāṣid al-syarī'ah includes five main principles: the preservation of religion, soul, mind, offspring, and property, all of which emphasize the importance of prohibiting and punishing practices that insult human dignity such as necrophilia. Criminalizing necrophilia is an important effort to preserve religious integrity, morality, and social justice, as well as protect human dignity and the stability of society.